Safety, effectiveness and hesitancy of COVID-19 vaccination in children: A cross-sectional study in Pakistan - Zaufishan, Zaufishan; Usman, Muhammad; Fishan Mumtaz, Khandah; Bilal, Rabiea; Arshad, Alina; Khan, Humaira Majeed (Frontiers in Public Health, 2023)
Background: The elevated risk of serious complications like myocarditis and pericarditis after COVID-19 vaccination, especially in adolescent has been reported in some instances that need to be tested in regional populations and different ethnicity groups. The purpose of the study was to evaluate the side effects, hesitancy, and effectiveness outcomes following COVID-19 vaccination among children in Pakistan. Methods: Study was planned using a cross-sectional design and data of Children and Adolescents (CA) was collected through convenient sampling method using a validated questionnaire between February to July 2022. A total of 1108 CA between the age of 12 to 18 years who received one or two doses of vaccine were selected and data was collected through direct interviews with respondents. Results: The results shown that among 99.8% respondents received Pfizer COVID-19 vaccine, 72.3% respondents were partially vaccinated (with one dose) while 27.7% were fully vaccinated (with two doses). COVID vaccination regime had a favorable safety profile in children as compared to adults. The vaccine hesitancy in children was reported to be 52.4% and the most common reasons of hesitance were assumption that vaccine is not safe (23.7%), vaccine is not required (19.6%) and vaccine is not effective (10.4%). The reported side effects were mainly of mild in nature (88.5%) followed by moderate (10.6%) and only 0.8% were of severe intensity. Post vaccination local side effects of mild intensity were common with an onset of average 24 hours (68%) and duration of 2-3 days (60.6%). The reported side effects were significantly associated with gender (p=0.00) while age had no significant effect on the occurrence of side effects. Overall, the vaccine was well tolerated by children and adolescents and was effective in preventing the reoccurrence of COVID-19 infection in 99.9% of participants. Conclusion: COVID-19 vaccine by Pfizer approved by FDA for use in CA 12 to 18 years of age was well tolerated with good safety profile and no serious adverse drug reactions was reported. The vaccine side effects were mild (88.5%) and lasted for an average of 2-3 days only (60.4%). The vaccine was effective is in safeguarding Children against COVID-19 infection.